Simultaneous profiling of histone modifications and DNA methylation via nanopore sequencing - Yue, Xue; Xie, Zhiyuan; Li, Moran; Wang, Kai; Li, Xiaojing; Zhang, Xiaoqing; Yan, Jian; Yin, Yimeng (Nature communications, 2022)
The interplay between histone modifications and DNA methylation drives the establishment and maintenance of the cellular epigenomic landscape, but it remains challenging to investigate the complex relationship between these epigenetic marks across the genome. Here we describe a nanopore-sequencing-based-method, nanoHiMe-seq, for interrogating the genome-wide localization of histone modifications and DNA methylation from single DNA molecules. nanoHiMe-seq leverages a nonspecific methyltransferase to exogenously label adenine bases proximal to antibody-targeted modified nucleosomes in situ. The labelled adenines and the endogenous methylated CpG sites are simultaneously detected on individual nanopore reads using a hidden Markov model, which is implemented in the nanoHiMe software package. We demonstrate the utility, robustness and sensitivity of nanoHiMe-seq by jointly profiling DNA methylation and histone modifications at low coverage depths, concurrently determining phased patterns of DNA methylation and histone modifications, and probing the intrinsic connectivity between these epigenetic marks across the genome. The interplay between histone modifications and DNA methylation plays a crucial role in establishing and maintaining the epigenomic landscape. Here, the authors develop a nanopore sequencing based method for mapping histone modifications and DNA methylation from native, long, single DNA molecules.